Editorial 15.5 - Percy, Alisa; Kelder, Jo-Anne (Journal of University Teaching and Learning Practice, 2018)
Welcome to the final issue for the Journal of University Teaching and Learning Practice for 2018. In this issue, we have papers from Australia, the US, and Ireland, covering topics related to information and academic literacy, self-efficacy, the flipped classroom, student engagement and their perceptions of group work. We would like to extend our gratitude to the reviewers for this issue: Amy Arnold, Pauline Bremmer, Ann Lawless, Amy Catalano, Sarah-Jane Gregory, Siti Halili, Elizabeth Handsley, Aguilar Katya, Cynthia Phillips, Vikki Pollard, Brenda Refaei, James Tsatsaronis, Margie Wallin, and Gail Wilson. We would also like to acknowledge the Journal’s Associate Editors: Peter Copeman, Andrew Kelly, Tracey Kuit, Kwong Sim Nui, Vikki Pollard, and Holly Tootell.